Approaching Complete Inhibition of P-Glycoprotein at the Human Blood–Brain Barrier: An (R)-[11C]Verapamil PET Study. Issue 5 (May 2015) - Bauer, Martin; Karch, Rudolf; Zeitlinger, Markus; Philippe, Cécile; Römermann, Kerstin; Stanek, Johann; Maier-Salamon, Alexandra; Wadsak, Wolfgang; Jäger, Walter; Hacker, Marcus; Müller, Markus; Langer, Oliver
As P-glycoprotein (Pgp) inhibition at the blood–brain barrier (BBB) after administration of a single dose of tariquidar is transient, we performed positron emission tomography (PET) scans with the Pgp substrate ( R )-[ 11 C]verapamil in five healthy volunteers during continuous intravenous tariquidar infusion. Total distribution volume ( V T ) of ( R )-[ 11 C]verapamil in whole-brain gray matter increased by 273 ± 78% relative to baseline scans without tariquidar, which was higher than previously reported V T increases. During tariquidar infusion whole-brain V T was comparable to V T in the pituitary gland, a region not protected by the BBB, which suggested that we were approaching complete Pgp inhibition at the human BBB.